2019
DOI: 10.5194/asr-16-229-2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of five different methods for the estimation of surface photosynthetically active radiation from satellite imagery at three sites – application to the monitoring of indoor soft fruit crops in southern UK

Abstract: Abstract. This paper assesses several methods for the retrieval of Photosynthetically Active Radiation (PAR) from satellite imagery. The results of five different methods are compared to coincident in-situ measurements collected at three sites in southern UK. PAR retrieval methods are separated into two distinct groups. The first group comprises three methods that compute PAR by multiplying the satellite-retrieved solar broadband irradiance at the surface (SSI) by a constant coefficient. The two methods in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This work extended the validation initiated in 2018 [32]. In the previous work, five methods to assess PAR from satellites were developed and evaluated at three sites in the United Kingdom.…”
Section: Methods To Derive Par From Satellite Imagerymentioning
confidence: 85%
See 3 more Smart Citations
“…This work extended the validation initiated in 2018 [32]. In the previous work, five methods to assess PAR from satellites were developed and evaluated at three sites in the United Kingdom.…”
Section: Methods To Derive Par From Satellite Imagerymentioning
confidence: 85%
“…This paper aimed to check whether the conclusion previously drawn could be extended to a much wider set of sites in Europe, Africa, the Middle East, and South America. In Thomas et al [32], two surface solar irradiance (SSI) resources, HelioClim-3 version 5 (HC3) and the Copernicus Atmosphere Monitoring Service radiation product in allsky conditions (CAMS-Rad), were utilized. Both resources relied on CAMS McClear for cloud-free conditions [23,25].…”
Section: Methods To Derive Par From Satellite Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as a work-around, several authors have suggested a variety of models to estimate the different components of PAR. PAR components can be estimated using atmospheric radiative transfer models (ARTM), e.g., Bird and Riordan (1986), Gueymard (1995) or Emde et al (2016) and methods derived from these, e.g., Wandji et al (2019) or Thomas et al (2019). However, since ARTM is associated with high complexity and using it demands much knowledge in atmospheric sciences, most of the models are empirical.…”
Section: Introductionmentioning
confidence: 99%